ANALISIS ESTIMASI HARGA LAHAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS DI KECAMATAN DAYEUHKOLOT KABUPATEN BANDUNG - Yusifa Muzri; Lili Somantri; Iwan Setiawan (Geography Education Study Program, Universitas Samudra, 2022)
The high changes in land values ​​and land use unwittingly continue to increase along with the increasing demand for land. The condition of the land in Dayeuhkolot District was initially used for agricultural land then became the residential sector, industry and so on. Seeing these conditions, it is necessary to map land price estimates. Mapping of land price estimates is certainly influenced by certain factors such as land use (rice fields, settlements, plantations), positive accessibility (roads, government), negative accessibility (rivers, industry, and cemeteries). In this study, using a Geographic Information System, all parameters are processed using the Scoring (Weighting) technique and then through the Overlay and Buffering stages. The purpose of this study is to determine the price of land with the final result in the form of an Estimation Map of Land Prices in Dayeuhkolot District.